Shades of care: Understanding the needs of racially and ethnically diverse paediatric patients, their families, and health care providers in North America. (March 2023) - Ladha, Raisa; Neiterman, Elena
While race and ethnicity have been acknowledged as determinants of health, there remain gaps regarding their effects on experiences of paediatric care. This scoping review examines empirical literature regarding the state and experience of paediatric care provided to racially and ethnically diverse families in North America. We seek to clarify the needs of care administrators and recipients, as well as to conceptualize what paediatric care must look like to enable equitable practices and optimal health outcomes. Utilizing Arksey and O'Malley's framework, we reviewed literature published between 2005 and 2020, most of which was written within an American context. The literature reviewed featured quantitative, qualitative and mixed methods studies. Paediatric care administrators and recipients collectively identified the following as domains requiring an increased focus: (1) knowledge (awareness or training), (2) alignment of views and values, (3) resources and (4) communication. Findings suggest overall that despite there being merit in the cultural competency efforts underway, more patient-centric approaches are vital. This review concludes by encouraging the sustained development of cultural safety initiatives in paediatric care to ultimately promote patient comfort and provider-patient collaboration.